Empathic Cultural Mapping: Little data, big data, knowledge transfer and exchange - Goopy, Suzanne; Turin, Tanvir; Kassan, Anusha; O'Brien, Mary; McCormack, Gavin; Chapman, Jonathan; Charania, Irina; Ferreira, Carla; Silversides, Halley (International Journal of Population Data Science, 2018)
Introduction A healthy city is one that continually creates and improves psychosocial and social environments and expands community resources allowing people to develop to their maximum portential. The role of SEDoHs is incontestable, yet we continue to face many of the same SEDoH-related problems despite what we know. Objectives and Approach This project presents the idea of "Empathic Cultural Mapping" (ECM). ECM is an interactive story map which brings together vignettes taken from individual stories curated with "big data" derived from places such as Statistics Canada, the City of Calgary, and library holdings at the University of Calgary. ECM seeks to challenge users to re-imagine long held constructions around sectoral, and disciplinary driven interpretations and categorizations of lifestyle, consumption, health, and the environment. ECM seeks to encourage knowledge users from multiple sectors to think beyond what is known and to consider what might be possible. Results ECM is a creative interactive undertaking. In developing ECM, a range of creative research processes have been used to record and tell the stories of a small group of newcomers (defined as those who migrate, seek refuge, or claim asylum in Canada) and position these within large data. A desire to improve the health and wellbeing of individuals and communties through opening processes of dialogoue between local government, non-government organizations, communitites, and individuals lies at the heart of this project. Knowledge and sense-making are key features of individual and community empowerment within the ECM and are viewed as powerful stimuli for change as well as powerful allies for health and a buffer against its threats. Conclusion/Implications ECM creates, shares, and brings together individual stories and 'big data'. It identifies needs that impact health in the everyday. It seeks to improve awareness of the world around us. It encourages people to communicate their experiences. Finally, it achieves its goals by using creative processes.